2006
DOI: 10.1248/yakushi.126.209
|View full text |Cite
|
Sign up to set email alerts
|

α1-Adrenoceptor Subtype Selectivity and Organ Specificity of Silodosin (KMD-3213)

Abstract: The selectivity of silodosin , an antagonist of a 1 -adrenoceptor (AR), to the subtypes (a 1A -, a 1B -and a 1D -ARs) was examined by a receptor-binding study and a functional pharmacological study, and we compared its subtype-selectivity with those of other a 1 -AR antagonists. In the receptor-binding study, a replacement experiment using [ 3 H]-prazosin was conducted using the membrane fraction of mouse-derived LM (tk-) cells in which each of three human a 1 -AR subtypes was expressed. In the functional phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 18 publications
(3 reference statements)
0
59
1
Order By: Relevance
“…The potencies of the various α1-adrenoceptor antagonists in our study would presumably be reflected by their clinical efficacies towards stone passage. The efficacies displayed by silodosin in the present experiments on the mouse ureter (pKB value = 9.47) and hamster ureter (10.09) were much greater than those reported for the mouse aorta (α1D-adrenoceptor-mediated response; pA2 value = 8.25) (Hosoda et al, 2005), rat aorta (α1D-adrenoceptor-mediated response; pA2 value = 7.88) (Tatemichi et al, 2006a), dog carotid artery (α1B-adrenoceptor-mediated response; pKB value = 7.54) (Tatemichi et al, 2006b), or human mesenteric artery (α1B-adrenoceptor-mediated response; pA2 value = 7.47) (Murata et al, 2000). Moreover, Akiyama et al (1999) demonstrated in anesthetized rats that silodosin suppressed an α1A-adrenoceptor-mediated response (the increase in intraurethral pressure induced by phenylephrine) without seriously altering mean blood pressure, with selectivity (α1A-adrenoceptor-mediated response against hypotensive effect) being markedly greater for silodosin (29.7) than for terazosin (0.52).…”
Section: Discussioncontrasting
confidence: 74%
“…The potencies of the various α1-adrenoceptor antagonists in our study would presumably be reflected by their clinical efficacies towards stone passage. The efficacies displayed by silodosin in the present experiments on the mouse ureter (pKB value = 9.47) and hamster ureter (10.09) were much greater than those reported for the mouse aorta (α1D-adrenoceptor-mediated response; pA2 value = 8.25) (Hosoda et al, 2005), rat aorta (α1D-adrenoceptor-mediated response; pA2 value = 7.88) (Tatemichi et al, 2006a), dog carotid artery (α1B-adrenoceptor-mediated response; pKB value = 7.54) (Tatemichi et al, 2006b), or human mesenteric artery (α1B-adrenoceptor-mediated response; pA2 value = 7.47) (Murata et al, 2000). Moreover, Akiyama et al (1999) demonstrated in anesthetized rats that silodosin suppressed an α1A-adrenoceptor-mediated response (the increase in intraurethral pressure induced by phenylephrine) without seriously altering mean blood pressure, with selectivity (α1A-adrenoceptor-mediated response against hypotensive effect) being markedly greater for silodosin (29.7) than for terazosin (0.52).…”
Section: Discussioncontrasting
confidence: 74%
“…Moreover, tamsulosin has a higher selectivity for the α1B-adrenoreceptors than silodosin, and thus, the decrease in blood pressure induced by tamsulosin may be mediated by its blocking α1B-adrenoreceptors action on the participating in blood vessel contraction and baroreceptor-induced inotropic effects. [9,16] Therefore, the lack of cardiovascular side effects may be a major advantage of silodosin. Our study statistically proved that silodosin is effective in improving the IPSS, PFR with fewer cardiovascular side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Silodosin is an emerging agent with high selectivity for α1A-ARs recently developed in Japan. In vitro studies have showed that silodosin's α1A-to-α1B binding ratio is extremely high (162:1) [9]. Schwinn DA et al [10] , Forray C et al [11] compared silodosin with non-selective alpha1A-adrenoceptor (AR) blockers and demonstrated that drugs with a high selectivity for α1A-Adrenoreceptors may be more prostatespecific and maintain a therapeutic response in the treatment of symptomatic BPH with minimal effect on blood pressure and fewer cardiovascular side effects .…”
Section: Introductionmentioning
confidence: 99%
“…Silodosin was demonstrated to have a higher selectivity for the alpha 1A -AR subtype than tamsulosin hydrochloride, naftopidil or prazosin hydrochloride, and the alpha 1A -to-alpha 1B binding ratio of silodosin is 162 : 1. 13 These results suggested that silodosin may have more beneficial effects on the symptoms associated with BPH and minimal effects on blood pressure. Several randomized controlled trials have reported the clinical effectiveness and safety of silodosin for BPH.…”
Section: Introductionmentioning
confidence: 95%
“…[32][33][34] Moreover, tamsulosin has a higher selectivity for the alpha 1B -AR than silodosin, and thus, the decrease in blood pressure induced by tamsulosin may be mediated by its blocking action on the alpha 1B -AR participating in blood vessel contraction and baroreceptor-induced inotropic effects. 13,24 Therefore, the lack of cardiovascular side effects may be a major advantage of silodosin.…”
Section: Wilt and Colleaguesmentioning
confidence: 99%